A Comment on "Preference Discovery in University Admissions: The Case for Dynamic Multioffer Mechanisms" - Paul Rosmer (Institute for Replication (I4R), 2024)
Grenet et al. (2022) examine the effect of quasi-random early offers on the probability of accepting an offer in the Germany's university admission process. The authors demonstrate that the early offers lead to a statistically significant increase in the likelihood of accepting an offer. Their preferred explanation for this early-offer effect is that students gradually discover their preferences over time, a hypothesis also supported by survey data. First, we successfully computationally reproduce the main claims of the paper in STATA. Second, we reproduce the results in R, including producing the analysis data from scratch. Third, we test the robustness of the results by checking the identification assumption with new data, applying different standard errors for the main estimation, and using an alternative empirical model specification.
Keywords: 330